Mechanical systolic time is shortened in highly trained athletes - Di Giacinto, B.; Quattrini, F. M.; Emanuele, G.; Caselli, S.; Di Paolo, F. M.; Pisicchio, C.; de Blasiis, E.; Ciardo, R.; Pelliccia, A.; de Castro, S. (Archivos de medicina del deporte, 2008)
We sought to evaluate the systolic time duration comparatively in elite athletes and sedentary healthy controls by 3-dimensional echocardiography (3DE). Methods: 100 athletes, engaged in endurance (n=66) and mixed disciplines (n=34) and 46 sedentary controls, matched for age, underwent 3DE examination with high frequency recording (28 ± 3 Hz). By semi-automatic analysis, volume time curves were generated; time from the beginning of the QRS complex to the minimum systolic volume (TMSV, msec) was the mechanical systole. Values of TMSV were also expressed as percent of the heart cycle (TMSV%). Results: Heart rate was lower both in endurance (52 ± 7 bpm; p<0.001) and mixed disciplines athletes (55 ± 7 bpm; p<0.001) as compared to controls (71 ± 4 bpm; p<0.001). Left ventricular end-diastolic volume was signifi cantly higher in endurance (90.4 ± 12.6 ml/m2; p<0.001) and mixed athletes (75.2 ± 11.8 ml/m2; p<0.001) as opposed to controls (57.4 ± 10.9ml/m2). Mild, but signifi cant shortening of TMSV was identifi ed both in endurance athletes (335 ± 35 msec; p=0.01) and mixed disciplines (320 ± 37 msec; p=0.001) compared to controls (354 ± 28 msec). Lower values of TMSV% were observed both in endurance (28.8 ± 3.4%; p<0.001) and mixed athletes (29.4 ± 3.5%; p<0.001) as opposed to sedentary subjects (41.3 ± 3.3%; Figure 1). Finally, TMSV showed a positive correlation with heart rate at rest (r=0.57; p<0.001). Conclusion: Elite athletes show a mild but signifi cant shortening of mechanical systole in comparison to healthy sedentary controls. This adaptation may explain, in addition to lengthening of diastolic time, an increased myocardial performance (Figure 1).